Energy Production from Maize - Piementel, David (Problemy Ekorozwoju, 2012)
All biofuels produced in the world utilize food resources. This contributes to the world starvation problem that is reported to be more than 66% of the world population being malnourished. Starvation is the number one cause of death in the world. Approximately 40% of U.S. corn is being converted into ethanol and 1.6 liters of fossil oil equivalents are required to produce 1 liter of ethanol. Thus, the U.S. is importing oil to produce ethanol at an enormous economic and fuel cost to the people of the nation, and reduces food resource availability to the people.